Intrasentential binding and extrasentential binding in child and adult Korean. Issue 6 (December 2019) - Joo, Kum-Jeong; Ud Deen, Kamil
This article investigates the binding properties of the Korean reflexive caki . Korean caki allows a local antecedent, a long-distance sentence-internal antecedent, and (unusually) an extrasentential antecedent. Two experiments were conducted with Korean-speaking child participants (mean age = 5;8; age range = 5;1–6;4) and adult controls. The first tested local binding versus long-distance intrasentential binding, and the second tested extrasentential binding. The results show, first, that the children allowed both a local and a long-distance antecedent for caki, with a preference for the long-distance reading (counter to many claims that children show a robust preference for local antecedents crosslinguistically). Second, the children allowed caki to refer to an antecedent in a preceding sentence. These results indicate that, at an early stage, Korean children have acquired adult-like knowledge of the complex properties of caki, including what might be considered the computationally taxing option of extrasentential binding.